Neonatal meningitis caused by Elizabethkingia meningoseptica in Saudi Arabia - Amer, Malaka Z; Bandey, Manzour; Bukhari, Abdalla; Nemenqani, Dalal (The Journal of Infection in Developing Countries, 2011)
Elizabethkingia meningoseptica is a multi-drug resistant organism that can cause meningitis in premature neonates. We report a case of Elizabethkingia meningoseptica meningitis that was detected early in an extremely premature low birth weight infant. He was successfully treated with a combination of ciprofloxacin and piperacillin-tazobactam. The spread of infection was controlled with no other reported cases.